Genetic-algorithm optimization of the analysis of elastic scattering of light nuclei based on the S-matrix model - Korda, V.Yu.; Shlyakhov, N.A. (Вопросы атомной науки и техники, 2000)
A genetic algorithm for an optimization problem in nuclear physics is discussed.